ZORA 156: Razgledi po slovenski moderni: Nacionalni, večkulturni in medkulturni koncepti, kratka proza in poezija - Čeh Steger, Jožica (University of Maribor Press, 2024)
ZORA 156: Views of the Slovene Moderna: National, Multicultural and Inter-Cultural Concepts, Short Prose and Poetry. The scientific monograph Views of the Slovene Moderna brings to the forefront findings of literary creators affiliated to various literary styles and different stylistic currents from the Slovene Moderna stylistic period. The research field incorporates writers whose literary works emerged on the horizon of new literary currents and styles, the decadence, symbolism, neo romanticism, impressionism and secession, as well as those who at the turn of the 20th century still remained in the framework of realistic-naturalistic poetics: Ivan Cankar, Oton Župančič, Fran Govekar, Izidor Cankar, Alojz Kraigher, Ljudmila Poljanec, Ivo Šorli, Fran S. Finžgar, Franc Ksaver Meško, Rudolf Maister, Alojzij Remec and Kristina Šuler. A particular asset of this monograph is that alongside the national concept, it also considers the multi-cultural and inter-cultural concept of literature of the Slovenian Moderna, while limiting itself to Slovene-German bi- and multi-culturalism (Gusti (Jirku) Stridsberg, Ana Wambrechtsamer, Rudolf Hans Bartsch).